Strategi Manajemen Komunikasi Dalam Upaya Meningkatkan Penjualan Produk Asuransi - Tri Azmi Ramadhani; Mutiara Sawitri Pane; Rifaldi Ahmad Nasution; Rio Rifki Panggabean; Zainarti Zainarti (STIT Sirojul Falah Bogor, 2023)
The idea behind marketing is finding out what customers want and need. As a result, to provide various product-related information to customers, marketers must be able to formulate policies that are supported by effective communication. As a result, designing consumer behavior requires a deeper understanding of communications, particularly marketing communications. This study aims to explain the field of marketing communications. Interacting with others can be made simpler by the availability of communication. There is no process of human life without communication. In other words, for everyone to achieve their goals, communication is essential for the exchange of ideas. Advertising, vendors, signs, shops, displays, product packages, free samples, coupons, giveaways and other marketing communication tools are examples. Impact marketing can also result in viral marketing via social networks such as Facebook due to shifts in consumer behavior. You can proceed both ways at any time and from any location thanks to it. . Keywords: Marketing Communication, Marketing, Consumer Behavior.